DESIGN OF LABM2M PLATFORM AS IOT (INTERNET OF THINGS) GATEWAY USING WEB SERVICE - Ahmada Itmamunnafi; Suryo Adi Wibowo; Nurlaily Vendyansyah (International Journal of Computer Science and Information Technology, 2024)
The creation of a platform is one of the advancements in technology and the internet which refers to industrial 4.0, to implement industrial 4.0 one of the main supporting factors is the availability of digital infrastructure. One of them is the internet of things (IoT). IoT itself refers to a network of physical devices, vehicles, household appliances, and other items that are embedded with electronic devices, software, sensors, actuators, and connectivity that make it possible to connect to the internet network and collect and exchange data. However, IoT devices have certain limitations on their storage loads and computing power. Storage refers to how and where data will be stored, while computing power refers to processing power, memory, network, and is processed in such a way that it is displayed to end users and has the ability to transfer data over the network without requiring human-to-human (P2P) interaction. or human to computer (P2M). Judging from the existing limitations, there is a way out, namely by using PaaS (platform as a service) which utilizes web services as the main foundation of this IoT Gateway. Where end users can integrate IoT projects that are being developed easily and quickly without thinking about the storage load and computing power limitations. To find out the performance of the system created, an analysis is carried out by monitoring simultaneously and using different devices. And the system is able to handle every request and response from the client.